“MUCH OF WHAT WE LEARN ABOUT INDIANS, WE LEARN AS CHILDREN”: COUNTER-IMAGES TO BIASED AND DISTORTED PERCEPTIONS OF FIRST NATIONS IN NATIVE CANADIAN JUVENILE LITERATURE - Amante, Susana (2015)
In Canada, many spelling and arithmetic books, as well as other simple books for school beginners perpetuate numerous falsehoods about Native peoples, which need to be eradicated. First Nations are not heathen savages always carrying tomahawks, bows and arrows, nor are they objects to be counted along with apples and balls. Scrutinising reading materials is crucial to ensure that books accurately reflect Native values and world views, instead of promoting ignorant myths that contribute to biased perceptions of Others and even of ourselves. It is with this in mind that, in my paper, I intend to reflect upon a children’s picture book written by Thomas King, because it represents conscious efforts on the part of its author to correct the above-illustrated stereotypes, thus providing Native and non-Native peoples with authentic and clearer representations of the First Nations of Canada.